1995
DOI: 10.1016/0043-1354(94)00250-b
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera seeds for softening hardwater

Abstract: The coagulant and disinfectant qualities of Moringa oleifera and Citrus paradisi were investigated on various water samples acquired from sachet water (packaged water), borehole water, river water and well water. The results revealed that Moringa oleifera functioned adequately at settling time beyond 2 h in highly turbid river water but was more effective when combined with Citrus paradisi. Moringa oleifera or its combination with Citrus paradisi is less effective for turbid water treatment but effective for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
3
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 10 publications
3
82
3
10
Order By: Relevance
“…The results of Katayon et al (2004Katayon et al ( , 2005Katayon et al ( , 2006a and Muyibi and Evison (1995b) indicated that M. oleifera seed extract may not be an efficient coagulant for low turbid water. However, the extract of M. oleifera seed was used to reduce the hardness to 70.00 % as well as turbidity to 99.00 % in hard water (Muyibi and Evison 1995a). Furthermore, the extract efficiency of M. oleifera seed for turbidity removal equals that of alum according to the study conducted by Muyibi and Alfugara (2003).…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The results of Katayon et al (2004Katayon et al ( , 2005Katayon et al ( , 2006a and Muyibi and Evison (1995b) indicated that M. oleifera seed extract may not be an efficient coagulant for low turbid water. However, the extract of M. oleifera seed was used to reduce the hardness to 70.00 % as well as turbidity to 99.00 % in hard water (Muyibi and Evison 1995a). Furthermore, the extract efficiency of M. oleifera seed for turbidity removal equals that of alum according to the study conducted by Muyibi and Alfugara (2003).…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…It has been described as adsorption and charge neutralization (Ndabigengesere et al, 1995;Gassenschmidt et al, 1995) and interparticle bridging (Muyibi and Evison, 1995a). Flocculation by inter-particle bridging is mainly characteristic of high molecular weight polyelectrolytes.…”
Section: Moringa Seeds As Coagulantmentioning
confidence: 99%
“…have reported its use as a coagulant (Jahn and Dirar, 1979;Muyibi and Evison, 1995;Jahn, 1986Jahn, , 1988Folkard et al, 1992); a softening agent (Muyibi et al, 2003); and a bactericidal agent (Madsen et al, 1987;Eilert et al, 1981;Kalogo et al, 2000). Thilza et al (2010) reported that Moringa leaf stalk extract had Afr.…”
Section: Introductionmentioning
confidence: 99%
“…Berger et al (1984) in a study on the toxicology of M. oleifera seed concluded that it may not constitute a serious health hazard. Muyibi and Evison (1995) suggested that further studies need to be carried out to ensure the complete safety of using M. oleifera in water treatment. Folkard et al (1989) however reported that to date, all the studies have concluded that there is no evidence to suggest any acute or chronic effects on humans, particularly at the low doses required for water treatment.…”
Section: Introductionmentioning
confidence: 99%